Radioactive convergence of nuclear leakage in Fukushima: Economic impact analysis of triple tragic events - Yorucu, Vedat; Katircioglu, Salih Turan (Pergamon-Elsevier Science Ltd, 2014)
The novelty of this study is to investigate if there is radioactive convergence around Fukushima city of Japan as a result of earthquake and tsunami in March 2011. The research also aims to investigate whether the other nearby cities located around Fukushima city shared any common convergence experience following the first two weeks of the March 2011 explosion, which all might be affected by this tragic chain of events. Two kinds of convergence have been examined: beta and sigma. For the entire period of 15-27 March 2011, only sigma convergence has been observed. The research findings did not confirm any beta convergence for the entire period. However, for the sub-periods (first week, first half and second half of the second week), more significant results have been found both for beta and sigma convergences of radioactive contamination. The data used in this study covers the period of 15-27 March 2011 on hourly bases in order to analyze the catching-up process between six cities surrounding Fukushima which are affected from the catastrophe. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fukushima's nuclear crisis; Beta/sigma radioactive convergence; Japan